Cost Effectiveness of Reproductive Health Interventions in Uganda: The Case for Family Planning services - Ssewanyana, Sarah; Kasirye, Ibrahim (The African Economic Research Consortium, 2013)
There seems to be a consensus among policymakers and politicians that innovative interventions have to be put in place to reduce the population growth rates in Uganda. The country’s population growth rate of 3.2% per annum is extremely high — even for a low income country. The above scenario is attributed to high number births per woman as measured by the Total Fertility Rate (TFR) and this has remained substantially above levels elsewhere in sub‐Saharan Africa (SSA). For example, in 2006 Uganda’s TFR of 6.7 births per woman was higher than the SSA average of 5.5 births per woman. On the other hand, with an annual per capita Gross Domestic Product (GDP) of US$ 300, Uganda remains one of the poorest countries in SSA. Furthermore, due to the predominance of informal activities and weak tax administration system, the country collects only 13.7 % of its GDP in taxes. As such the amount of funds available for financing health services in general and reproductive health services in particular are limited.